The Student’s Perceptions of the Media Used by Teacher in Teaching English at SMP N 4 Pematang Raya - Swasti Lumbanraja; Sahlan Tampubolon; Rina Octavia S imarmata; Nurliani Siregar; Mula Sigiro (Innovative: Journal Of Social Science Research, 2023)
This research aimed to find out (1) The kinds of media used by the teacher in teaching English; (2) The students perception of the media used by the teacher in teaching English. The data were conducted on February 2023 from 30 students of the eighth-grade students at SMP N 4 Pematang Raya from two classes. This used a descriptive qualitative research; the instruments were an observation and question are. The observation was used to observe the teacher of the eighth-grade students at SMP N 4 Pematang Raya and the questionnare was distributed to the students of the eighth-grade. The findings of this research showed that the kinds of media used by the when teaching English were a whiteboard, English book, dictionary, laptop, LCD Projector, and speaker. The result of the students questionnaires that most of the students gave positive perception toward the media used by English teacher in teaching and learning process, they were being happy, being more active, being more excited/spirit in learning English, they were easier to understand the materials, they can repair their pronunciation, vocabulary, find new ideas, express their opinion and they can practice it in daily life. Whereas there were also some students gave negative perception toward the media used by English teacher in teaching and learning process that they cannot be enthusiastic and spirit to learn English, pronounce the words correctly, find new ideas and express their opinion because they were lazy, being wary and afraid of being wrong in learning English.